Environmental acclimatization of the relatively high latitude scleractinian coral Pavona decussata: integrative perspectives on seasonal subaerial exposure and temperature fluctuations - Man Zhang; Shan Huang; Li Luo; Kefu Yu (BMC Genomics)
Abstract Background Coral reefs are being increasingly threatened due to global climate change. However, some coral species have shown strong tolerance despite living in marginal environments. The species Pavona decussata from Weizhou Island in the South China Sea experiences subaerial exposure in summer and winter due to extreme low tides, and their environmental acclimatization to this aerial exposure remains unexplored. Results Here we aimed to explore the molecular mechanism of P. decussata under season or subaerial exposure background through physiological and multi-omics integrative analyses. Specifically, corals with a history of seasonal air exposure underwent comprehensive changes in energy metabolism and defense mechanisms compared to permanently submerged corals. In summer, corals experiencing subaerial exposure enhanced antioxidant defense by increasing the activities of the enzymes T-SOD and CAT, and the coral-associated bacterial community shifted toward the class Alphaproteobacteria that may have provided corals with resistance to environmental stresses. Moreover, the decrease in the transcript levels of the TCA cycle and the increase in metabolite content of ornithine suggested an alteration in energy metabolic pathways. Corals with an air-exposed background may have enhanced energy reserves in winter, as indicated by a higher content of Chl a and a rebound in coral-associated bacterial community toward the class Gammaproteobacteria. Furthermore, accumulation of the metabolite leukotriene D4 and activation of the TGF-beta signaling pathway suggested higher anti-inflammatory requirements and positive regulation by innate immunity. Conclusions This study provides insights into the acclimatization of P. decussata to seasonal environmental fluctuations and demonstrates that relatively high-latitude corals possess the plasticity and acclimatory capacity to adapt to marginal environments.